Use of a Scientific Approach in Improving Understanding of Surah At-Tiin In Class V Students of SD Negeri 1 Jugo in 2022 - Sudarmono; Fathoni, AB Musyafa'; Sufirmansyah (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
Education has an important role in the progress and future of the nation. This research aims to improve grade 5 students' understanding and memorization of Surah at-Tin through a scientific approach. In this research, the classroom action research method was used to search for data in the field. This research found that scientific methods have not been fully implemented by teachers, so students are bored and lack enthusiasm in following lessons. Apart from that, students' level of understanding and memorization is also weak. However, through the application of a scientific approach, students' understanding and memorization increased from 3 students in cycle 1 to 5 students in cycle 2. Thus, this research succeeded in increasing students' understanding and memorization of Surah at-Tin .